Which ordered pair is a solution to the system of equations? \( y=x+3 \) \( y=-2 x-3 \) \( (0,3) \) \( (0,-3) \) \( (-2,1) \) \( (1,2) \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To find the solution to the system of equations, we can substitute the values from each ordered pair into both equations. 1. For \( (0,3) \): - \( y = 3 \) and \( x = 0 \): - In the first equation: \( 3 = 0 + 3 \) (True) - In the second equation: \( 3 = -2(0) - 3 \) (False) 2. For \( (0,-3) \): - \( y = -3 \) and \( x = 0 \): - In the first equation: \( -3 = 0 + 3 \) (False) - In the second equation: \( -3 = -2(0) - 3 \) (True) 3. For \( (-2,1) \): - \( y = 1 \) and \( x = -2 \): - In the first equation: \( 1 = -2 + 3 \) (True) - In the second equation: \( 1 = -2(-2) - 3 \) (False) 4. For \( (1,2) \): - \( y = 2 \) and \( x = 1 \): - In the first equation: \( 2 = 1 + 3 \) (False) - In the second equation: \( 2 = -2(1) - 3 \) (False) The only ordered pair that satisfies both equations is \( (-2,1) \).